Pengaruh Coorporate Social Responsibility Disclosure Dan Institutional Ownership Terhadap Firm Value PT Sinar Pematang Mulia 11 Bandar Mataram Lampung Tengah - Andrianingsih, Retno Eka; Nusantoro, Jawoto; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Corporate Social Responsibility (CSR) Disclosure and Institutional Ownership on Firm Value at PT Sinar Pematang Mulia 11 Bandar Mataram Central Lampung. The type of research used is quantitative with this research method using panel regression method and processed using Eviews. The results showed that the Corporate Social Responsibility (CSR) Disclosure variable had a positive and significant effect on Firm Value, which was 0.000048 with a positive sign with a probability value of 0.0048 > 0.05. Institutional Ownership variable has a positive and significant effect on Firm Value, which is 0.000079 with a positive sign with a probability value of 0.0630 > 0.05. Corporate Social Responsibility (CSR) Disclosure and Institutional Ownership variables have a positive and significant impact on Firm Value, namely Fcount (3.696479) > from F table (2.934030) and probability value is 0.005279 < 0.05